2009
DOI: 10.1007/s12600-009-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium verticillioides as a new pathogen of the parasitic weed Orobanche spp.

Abstract: A strain of Fusarium verticillioides was isolated from the tubercles of the parasitic weed Orobanche cumana in Israel. The pathogenicity was tested in polyethylene bags on O. cumana, O. crenata, O. aegyptiaca and O. ramosa and in pots on O. cumana and O. crenata. F. verticillioides was highly pathogenic to O. aegyptiaca, O. ramosa and O. cumana in the polyethylene bags. In pots, the fungus caused wilting and necrotic areas on flowering shoots of O. cumana, but did not cause disease symptoms on O. crenata. F. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In general, three successive extractions are carried out with the same volume of solvent. 56,68,[76][77][78][79] In some cases, several extractions are carried out using successively hexane, chloroform, ethyl acetate and butanol due to their increasing polarity, to explore the widest diversity of metabolites. 70,76,80,81 This strategy allows a finer characterization of the metabolites because each fraction can be analyzed.…”
Section: Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, three successive extractions are carried out with the same volume of solvent. 56,68,[76][77][78][79] In some cases, several extractions are carried out using successively hexane, chloroform, ethyl acetate and butanol due to their increasing polarity, to explore the widest diversity of metabolites. 70,76,80,81 This strategy allows a finer characterization of the metabolites because each fraction can be analyzed.…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Commonly used organic solvents include ethyl acetate, butanol, chloroform, and hexane, among others. In general, three successive extractions are carried out with the same volume of solvent 56,68,76–79 . In some cases, several extractions are carried out using successively hexane, chloroform, ethyl acetate and butanol due to their increasing polarity, to explore the widest diversity of metabolites 70,76,80,81 .…”
Section: Methodological Approaches Used To Discover Identify and Expl...mentioning
confidence: 99%
See 1 more Smart Citation
“…After many years of study, there is no conclusive result or commercial application, even with breeding and release of adults. Other types of widely studied biocontrol agents are fungi [62] and bacteria [63] that have shown certain levels of control in pot studies under controlled conditions, but conclusive results from field studies have not yet been reported, highlighting above all the difficulty of finding a viable method of application and persistence [64]. The use of a series of natural metabolites produced by fungi or plants has also been proposed [65,66], which has shown an effect in the laboratory, but the mode of extraction or synthesis of these metabolites as well as their incorporation into the field must be optimized to make them applicable.…”
Section: Management Strategiesmentioning
confidence: 99%
“…In pots, the fungus caused wilting and necrotic areas on flowering shoots of O. cumana, but did not cause disease symptoms on O. crenata. The toxic metabolites were isolated and identified by spectroscopic methods as fusaric acid [23].…”
Section: Fungal Biocontrol Agentsmentioning
confidence: 99%